2019
DOI: 10.1080/22221751.2019.1687262
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel RhlI/R-PrrH-LasI/Phzc/PhzD signalling cascade and its implication in P. aeruginosa virulence

Abstract: Small regulatory RNAs (sRNAs) act as key regulators in many bacterial signalling cascades. However, in P. aeruginosa, the sRNAs involved in quorum sensing (QS) regulation and their function are still largely unknown. Here, we explored how the prrH locus sRNA influences P. aeruginosa virulence in the context of the QS regulatory network. First, gain- and loss-of-function studies showed that PrrH affects pyocyanin, elastase and rhamnolipid production; biofilm formation; and swimming and swarming motility and imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Upon binding with 3-oxo-C12-HSL and C4-HSL, the receptor proteins LasR and RhlR get activated and quickly activate the las and rhl systems. We thus investigated the influence of 3-oxo-C12-HSL and C4-HSL treatments on AmiL expression, with concentrations ranging from 5 to 40 μM according to reported studies that have demonstrated they can activate the las and rhl systems ( 25 , 43 45 ). Our data showed that even a high concentration of 3-oxo-C12-HSL had little influence on AmiL expression, whereas C4-HSL treatment dramatically inhibited its expression in a dose-dependent manner ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Upon binding with 3-oxo-C12-HSL and C4-HSL, the receptor proteins LasR and RhlR get activated and quickly activate the las and rhl systems. We thus investigated the influence of 3-oxo-C12-HSL and C4-HSL treatments on AmiL expression, with concentrations ranging from 5 to 40 μM according to reported studies that have demonstrated they can activate the las and rhl systems ( 25 , 43 45 ). Our data showed that even a high concentration of 3-oxo-C12-HSL had little influence on AmiL expression, whereas C4-HSL treatment dramatically inhibited its expression in a dose-dependent manner ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The EV pROp200, a Gm-resistant overexpression plasmid that can replicate stably in P. aeruginosa under the strong promoter P tac , was saved in our lab. This plasmid was used by Lu et al in our previous study to construct lasR or rhlR gene-overexpressing strains, named LasR + and RhlR + , respectively ( 25 ). These two strains were used in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, crcZ, which is related to carbon metabolism, is upregulated in the exponential phase but downregulated in the stationary phase, indicating that YbeY is involved in the growth phase-dependent metabolism regulation. The production of sRNA P27, PrrH, and NrsZ, involved in quorum sensing, was altered by the ybeY mutation (49)(50)(51). The RpoS-dependent sRNA RgsA, which regulates Fis and AcpP, is downregulated, which might be due to the defective expression of rpoS in the ybeY mutant (52).…”
Section: Discussionmentioning
confidence: 99%
“…Non-antibiotic methods against Pseudomonas aeruginosa include QS inhibitors: a narrative review AR mechanism of PA AR mechanism of PA is complex, and several factors are involved (9)(10)(11)(12): First, changes in cell membrane permeability: (I) high expression efflux pumps on the cell membrane of PA that transport drugs to the outside of cells; (II) the loss or low expression of membrane poreforming proteins: the main drug-resistant mechanism of carbapenems is the loss or decrease of outer membrane pore-forming protein OprD2. Second, the production of inactivated enzymes or modified enzymes on PA, such lactamase and aminoglycosidase.…”
Section: Review Articlementioning
confidence: 99%